Influence of electronic wastes on the wear and corrosion properties of aluminum matrix composites - Sezer, Rasit; Corbacioglu, Burcu Didem (WALTER DE GRUYTER GMBH, 2026)
In this study, the influence of electronic waste reinforcement on the properties of aluminum was investigated. For this purpose, samples were produced with hot pressing at 600 degrees C. The reinforcement ratio for the composites was determined as 1 wt.%, 5 wt.%, and 10 wt.%. The wear and corrosion behavior of the samples were investigated by dry sliding wear test and electrochemical corrosion tests. The wear rate values indicated that the increasing reinforcement ratio reduced the wear rate. Moreover, it was determined that the increasing reinforcement ratio improved the corrosion behavior of the composites. The corrosion rate of the samples was reduced with an increasing reinforcement ratio, and a more stable surface was obtained in corrosion environment. In conclusion, it was deduced that Rh, Ag, Pt, and Sn containing electronic waste provided significant improvements in wear and corrosion behaviors.
Keywords: aluminum; composite; electronic waste; corrosion; wear; FRACTURE-BEHAVIOR; ALLOY; MICROSTRUCTURE; FABRICATION; PREFORMS; FATIGUE; Materials Science